Dialogue Beyond Belief: The Role of Participation in Religious Practices as the Meeting Point for Muslim Christian Encounter. (July 2019) - Azdajic, Dejan
In spite of a commendable proliferation of Muslim-Christian initiatives in recent years, progress has been slow. Islam and Christianity are essentially two rival belief systems each claiming doctrinal and theological superiority. Any serious dialogue that goes deeper into these issues and attempts to discover new hermeneutical bridges inevitably reaches its explanatory limit. In this article, I argue that there may perhaps be new ways to overcome this historic standstill. Borrowing from insights gained from a sociological approach to the study of religion, it becomes evident that it is necessary to distinguish between religion as a set of normative beliefs and the concrete implementation of those beliefs through religious practices. The application of theory into authentic forms of embodied religiosity is the responsibility of believers themselves. They concretize the normative prescriptions through a contextualized, local interpretation that is both pragmatic and meaningful in order to make sense of their everyday lives. To understand religion intellectually, it is necessary to consider its fundamental anthropological dimension. Hence, the study of religion must ultimately include the study of human beings in their natural context and from their point of view. Moreover, I provide evidence that true insight is contingent upon actual participation in the religious practices themselves. Building on this argument, this article suggests that Muslim-Christian relations would significantly benefit from including shared participation in sacred religious performances as part of the strategy for a successful encounter.